Supplementation of Zinc and Vitamin E on Apparent Digestibility of Nutrient, Carcass Traits, and Mineral Availability in Broiler Chickens - Tera Fit Rayani; R. Mutia; Sumiati Sumiati (Faculty of Animal Science, Bogor Agricultural University, 2017)
The purpose of this study was to determine the effect of zinc (Zn) and vitamin E supplementations on apparent nutrient digestibility, carcass traits, and mineral availability of broiler in tropical environment. The experiment was arranged in a 3 x 3 factorial design with 4 replications in each treatment (10 birds each). The dietary treatments were the combination of doses of zinc (A1: 0 ppm, A2: 40 ppm, A3: 80 ppm) and vitamin E (B1: 0 ppm, B2: 125 ppm, B3: 250 ppm) supplementations. The variables observed were apparent nutrient digestibilities (apparent crude protein digestibility and apparent ether extract digestibility), carcass traits (final weight, the percentage of carcass weight, breast weight, thigh weight, wings weight, and back weight), meat bone ratio and mineral availability in the tibia (calcium [Ca], phosphorus [P], and zinc [Zn]). The results showed that apparent nutrient digestibility, carcass traits (the percentages of carcass, breast, thighs, wings, and back), meat bone ratio were not significantly influenced by the supplementation of zinc or vitamin E. The supplementation of 80 ppm of Zn and 0 ppm of vitamin E significantly (P<0.05) increased final weight of broiler. Supplementation of zinc alone and vitamin E alone in the diet significantly (P<0.05) increased calcium content of the tibia. In conclusion, supplementation of 80 ppm of Zn increased calcium content compared to control, but did not affect final weight and ether-extract digestibility. Supplementation of vitamin E at a dose of 125 ppm could increase calcium content of the tibia compared to control.